MONOPSONY POWER AND WORKER UTILITY IN THE 6X1 LABOR SCHEDULE - Maciel, Daniel Thomaz Giacomelli Nunes; Pérez, Barbara Yadira Mellado; de Siqueira, Rosicley Nicolao; de Moraes, Fabrício César; Rihbane, Fahim Elias Costa (ARACÊ, 2024)
This study analyzes the 6x1 work schedule, characterized by six consecutive workdays followed by one rest day, highlighting its economic and social impacts. It explores the interaction between firm-level profit maximization and worker utility, incorporating monopsony power in wage-setting and diminishing returns to labor productivity. Using a theoretical model, the study examines how long working hours affect worker health, morale, and productivity while influencing organizational outcomes. Findings reveal significant distortions in equilibrium wages and hours due to monopsony power, emphasizing the trade-offs between economic efficiency and worker well-being. The study calls for policies addressing these inefficiencies to ensure sustainable labor practices.